Youth as Educators: Cultivating Youth Digital Contribution to Community Education - Suryani, Adi; Soedarso, Soedarso; Muhibbin, Zainul; Wahyuddin, Wahyuddin; Saifulloh, Moh. (IJECA (International Journal of Education and Curriculum Application), 2022)
Frequently, youth are stigmatized as troublemakers and immature groups. Thus, they still need to be educated, nurtured, and supervised, especially in this millennial era. In spite of the negative label attributed to youth, youth are potential community educators, especially in this digital world. Their natural interest in social media and technology can be an investment to engage them in community education through digital works. This study aims to explore educational aspects that several young students emphasize and educate to their online peers and digital community through their digital works creation which they upload on YouTube. The study adopts qualitative methods and employs thematic analysis to examine 50 uploaded videos. The study reveals that digital works can be media for youth to educate character, non-violence, and environmental-health education to their peers and other communities. This also encourages youth to learn to be active and responsible citizens, undertake direct experiential learning processes, enhance their social media responsibility, provide role models for others, promote community well-being, and alleviate negative youth stigma.